Associação entre variáveis funcionais e insuficiência cardíaca após o infarto do miocárdio em ratos association between - Polegato, Bertha F [UNESP]; Minicucci, Marcos F [UNESP]; Azevedo, Paula S [UNESP]; Gonçalves, Andréa F [UNESP]; Lima, Aline F [UNESP]; Martinez, Paula F [UNESP]; Okoshi, Marina P [UNESP]; Okoshi, Katashi [UNESP]; Paiva, Sergio A. R [UNESP]; Zornoff, Leonardo A. M [UNESP] (Sociedade Brasileira de Cardiologia, 2016)
Background: Heart failure prediction after acute myocardial infarction may have important clinical implications. Objective: To analyze the functional echocardiographic variables associated with heart failure in an infarction model in rats. Methods: The animals were divided into two groups: control and infarction. Subsequently, the infarcted animals were divided into groups: with and without heart failure. The predictive values were assessed by logistic regression. The cutoff values predictive of heart failure were determined using ROC curves. Results: Six months after surgery, 88 infarcted animals and 43 control animals were included in the study. Myocardial infarction increased left cavity diameters and the mass and wall thickness of the left ventricle. Additionally, myocardial infarction resulted in systolic and diastolic dysfunction, characterized by lower area variation fraction values, posterior wall shortening velocity, E-wave deceleration time, associated with higher values of E / A ratio and isovolumic relaxation time adjusted by heart rate. Among the infarcted animals, 54 (61%) developed heart failure. Rats with heart failure have higher left cavity mass index and diameter, associated with worsening of functional variables. The area variation fraction, the E/A ratio, E-wave deceleration time and isovolumic relaxation time adjusted by heart rate were functional variables predictors of heart failure. The cutoff values of functional variables associated with heart failure were: area variation fraction < 31.18%; E / A > 3.077; E-wave deceleration time < 42.11 and isovolumic relaxation time adjusted by heart rate < 69.08.Conclusion: In rats followed for 6 months after myocardial infarction, the area variation fraction, E/A ratio, E-wave deceleration time and isovolumic relaxation time adjusted by heart rate are predictors of heart failure onset.
Association between functional variables and heart failure after myocardial infarction in rats
Keywords: Heart failure/complications; Myocardial infarction; Rats; Ventricular dysfunction